MANAJEMEN SUMBER DAYA MANUSIA DALAM PERSPEKTIF ISLAM - Anisyah Risky Nasution; Chuzaimah Batubara (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
Management in an Islamic perspective is a management practice that applies Islamic values in the company's management functions. The purpose of this study is to determine the application of sharia management in the recruitment, selection and training of professional employees. This study also analyzes management practices based on Islam in companies. The research used is a qualitative approach with descriptive analysis method. The owners and staff of Azalea Botanicals have an understanding of the mandala. Management in an Islamic perspective is a management practice that incorporates Islamic values into the company's management functions. The results show that about Islamic management, which applies to areas such as workforce planning, recruitment, selection, and training. Likewise, researchers found that the application of Islamic values in all company activities has a positive impact on employee religiosity and responsibility, as well as creating a Rahmatan Lil'alamin environment that is beneficial to many people